ความสามารถในการดูดซับยาของพอลิไอออนเชิงซ้อนไคโตซานและโซเดียมไคโตซานฟอสเฟต - พรพรรณ ปรีดานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The polyion complex particles were prepared based on chitosan (CTS) and sodium chitosan phosphate (Na-P-CTS). The shape of polyion complex particles was core-shell consisting of cationic polymeric core and anionic polymeric shell. Absorption capability of ionic drugs onto polyion complex particles was tested. Labetalol hydrochloride (La), Sodium diclofenac (Di) and Acetaminophen (Pa) were selected as the cationic, anionic and neutral model drugs, respectively. The percentage of drug absorption capability was examined and found that cationic drug, anionic drug and neutral drug could be absorbed onto the polyion complex particles about 0.0-0.7 % by particles weight. The surface charges of the polyion complex particle before and after drug absorption were determined by Zeta potential. Owing to electrostatic interaction, cationic drug was absorbed at the shell region of the polyion complex particles, whereas the anionic drug was absorbed around the core region of the polyion complex particles. For neutral drug, it was absorbed through out the polyion complex particles, due to the diffusion.